A Catalyst‐Free Domino Protocol for the Chemoselective Synthesis of Multifunctionalised Pyrroles in Aqueous Media via Nitroketene‐N, S‐Acetal Chemistry. Issue 23 (19th June 2018) - Chaudhary, Ankita; Khurana, Jitender M.; Khanna, Garima; Saroha, Mohit
Abstract: A series of novel 5‐(1‐methyl‐5‐(methylthio)‐4‐nitro‐2‐aryl‐1 H ‐pyrrol‐3‐yl)pyrimidine‐triones was chemoselectively synthesized in excellent yields via catalyst‐free three component domino reactions of arylglyoxal monohydrate, ( E )‐ N ‐methyl‐1‐(methylthio)‐2‐nitroethenamine and 1, 3‐dimethyl barbituric acid/ barbituric acid in aqueous media. The prominent features of the established protocol are its environmentally benign nature, avoidance of catalyst, ease of execution, column free separation, short reaction time, excellent yield of product, high atom economy and low E‐factor. Abstract : A sustainable and diversity oriented synthesis of novel pyrrole scaffold by reaction of arylglyoxal monohydrate, ( E )‐ N ‐methyl‐1‐(methylthio)‐2‐nitroethenamine and 1, 3‐dimethyl barbituric acid/ barbituric acid in water as reaction media under catalyst free conditions has been described.